Bio-electrochemical power generation from petrochemical wastewater using as substrates in microbial fuel cell - Sumaya, Sarmin (2020)
The petrochemical wastewater (PCW) from the acrylic acid plant possesses a very high chemical oxygen demand (COD) due to the presence of acrylic acid (AA) along with other organic acids. The treatment of PCW by conventional aerobic and anaerobic methods is energy-intensive. However, the treatment of PCW with concurrent power generation by employing microbial fuel cell (MFC) could be a potential alternative to solve the energy and environmental issues. The main hurdle for the treatment of PCW in MFC is to find out the suitable inoculum based on the substrate-inoculum interaction, to unravel the mechanism of electron transfer leading to the high power gen eration as well as high COD removal efficiency. The goal of the present work is to find out the suitable inoculum possessing electrogenic and fermentative properties, to elucidate the electron transfer mechanism and finally to investigate the anode charge transfer kinetics. MFCs were operated using PCW from local AA plant and anaerobic sludge (AS) as biocatalyst where AS was acclimatized to prepare effective inoculum. The predominated microbes were identified which include the electrogenic genera namely Pseudomonas aeruginosa (PA) and Bacillus cereus (BC) along with methanogenic archea Methanobacterium spp. The major constituents of the PCW, such as acrylic acid, acetic acid (ACA) and dimethyl phthalate (DMP) were used as feed for MFC to evaluate the substrate-inoculum interaction. The performance of the MFC was evaluated in terms of voltage/current generation as well as maximum power generation using polarization and power curve. Cyclic votammetry (CV) and electrochemical impedance spectroscopy (EIS) were employed to elucidate the kinetics of anode charge transfer and Nernst-Monod-ButlerVolmer model was used to validate and predict the performance of MFC. The results revealed that the mixed substrates with acclimatized AS could produce high power (0.78 W/m3) compared to AA with PA (0.24 W/m3), AA with BC (0.22 W/m3), ACA with PA (0.39 W/m3), ACA with BC (0.32 W/m3), DMP with PA (0.24 W/m3) and DMP with BC (0.21 W/m3 ) respectively. The power generation data was correlated with the microbial growth pattern which indicated the formation of substrates-inoculum based synergy in the mixed substrate-acclimatized AS system. The study was further extended to the real PCW which demonstrated that the PCW with an initial COD of 45,000 mg/L could generate power density of 850 mW/m2(at a current density of 1500 mA/m2) using acclimatized AS as biocatalyst. The COD removal efficiency and the coulombic efficiency (CE) were found to be 40% and 21%, respectively after 11 days of operation using initial COD of 45000 mg/L. CV investigations confirmed the role of pyocynin and hydroquinone as electron shuttles. While comparing the CV data of the biofilm and the inoculum free anolyte after 11 days of operation, the high redox peak current was observed for the latter case which clearly demonstrated the predominant role of indirect charge transfer mechanism for power generation using PCW and acclimatized AS. The charge transfer kinetics was elucidated using the Tafel slop. The kinetic parameters were evaluated by fitting the kinetic data in Nernst-Monod- Butler-Volmar model where the experimental COD and current density production was found to be in good agreement with the proposed model. The model can be used for optimization of the performance of the PCW-fed MFC. The results of the present study showed that the electrocatalytic activity of anaerobic sludge can be improved by acclimatization which can be effectively used for simultaneous power generation and treatment of PCW.